Vacancy-solute interactions in Cu, Ni, Ag, and Pd - U. Klemradt; B. Drittler; T. Hoshino; R. Zeller; P.H. Dederichs; N. Stefanou (Physical Review B, 1991)
We apply the Korringa-Kohn-Rostoker Green’s-function method and perform ab initio calculations based on local-density-functional theory for the vacancy-solute interaction energies in Cu, Ni, Ag, and Pd. In particular, we calculate the nearest-neighbor interaction of vacancies with 3d and 4sp impurities in Cu and Ni as well as with 4d and 5sp impurities in Ag and Pd. We also calculate the divacancy binding energies in these hosts. Further we demonstrate that the Hellmann-Feynman theorem with respect to the nuclear charge provides a useful tool to calculate and understand interaction energies. We discuss applications to jellium calculations for Cu and to the stability of larger agglomerates.